2022
DOI: 10.1007/s00426-022-01680-0
|View full text |Cite|
|
Sign up to set email alerts
|

Executive functioning moderates the decline of retrieval fluency in time

Abstract: citeas). AcknowledgmentsWe thank Lucia Slezáková and Zuzana Mokrá for help with data collection and data preparation.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…Beyond that, stimuli in fluency tasks (being it different categories or letters) suffer from stimulus-inherent confounds (e.g. number, frequency or taxonomic and thematic clarity of candidate words) which influence retrieval demands [ 32 , 89 , 100 ]. Another line of evidence suggests that common fluency measures of automatic (clustering) and controlled (switching) retrieval both capture executive processing to some degree, and the picture gets even blurrier when considering time spent performing the task [ 28 , 32 , 85 , 101 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Beyond that, stimuli in fluency tasks (being it different categories or letters) suffer from stimulus-inherent confounds (e.g. number, frequency or taxonomic and thematic clarity of candidate words) which influence retrieval demands [ 32 , 89 , 100 ]. Another line of evidence suggests that common fluency measures of automatic (clustering) and controlled (switching) retrieval both capture executive processing to some degree, and the picture gets even blurrier when considering time spent performing the task [ 28 , 32 , 85 , 101 ].…”
Section: Discussionmentioning
confidence: 99%
“…dissociates) to serially presented word stimuli. Previous research has shown that retrieving semantically dissociated words exerts substantially more cognitive effort and processing time than the FA task, which has been attributed to additional control demands pertaining to inhibition and response monitoring [29][30][31][32][33]. The putative engagement of the inhibitory mechanisms in the dissociative retrieval stems from the inherent need to suppress the automatic (but task-inappropriate) semantic activations and response candidates evoked by the stimulus words [10,11,34,35].…”
Section: The Associative-dissociative Retrieval Taskmentioning
confidence: 99%
See 1 more Smart Citation
“…The 60 s time constraint may have diminished participants' performance or inhibited deep semantic processing of the emotion words (Maule & Edland, 1997;Winkielman et al, 2018). A systematic manipulation of the task duration (e.g., 1 min vs. 5 min, as has been called for in verbal fluency tasks; Michalko et al, 2022) could clarify how time pressure impacts performance and how well scores track other variables of interest. That said, we would conceptualize allowing participants to fully list all known emotion words without a time limit as a separate construct (potentially "emotion vocabulary;" see L. Beck et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…These tasks are thought to assess specific executive functioning abilities, including word retrieval and processing speed, and are widely used in neuropsychological testing to evaluate cognitive functioning (Henry & Crawford, 2004; Henry et al, 2004; Jurado & Rosselli, 2007; Metternich et al, 2014; Shao et al, 2014). In the current study, we adapted these verbal fluency measures to assess how many emotion words people could generate in 60 s. By altering one aspect of the task (i.e., asking participants to generate emotion words) while retaining other aspects (e.g., a short time limit; Badre & Wagner, 2002; Michalko et al, 2022), we maintain consistency with prior verbal fluency measures. Conceptually, maintaining a short time limit also allows us to measure the psychological process that occurs when people must name their emotions in daily life with relative speed, such as when in conversations with others.…”
mentioning
confidence: 99%